Recirculation intervals of nutrient solution in hydroponic acclimatization of banana seedlings - Iumi da S. Toyosumi; Tibério S. M. da Silva; Tales M. Soares; Maurício A. Coelho Filho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the technical viability of using longer recirculation intervals of nutrient solution than those conventionally used for the acclimatization of Prata-Ana banana seedlings grown under hydroponic system. The experiment was carried out in a greenhouse of a banana plantlet production biofactory, in Cruz das Almas, Bahia, Brazil, in a randomized block design with four replications. The use of longer recirculation intervals of nutrient solution (0.75, 3.75, 5.75, 11.75, and 23.75 hours) than those commonly used for vegetables (0.25 hour) was evaluated in the present study in two seasons: winter and summer-autumn. The effect of increasing the interval of nutrient solution recirculation on plant growth was more pronounced when the temperature was higher, during the summer-autumn season. Considering the plant growth period between 15 and 20 days after transplanting, there was no effect of the recirculation frequency, showing the viability of using lower recirculation frequencies or only one recirculation per day in the first 15 days of plant growth. However, the use of shorter intervals after this period is needed because the use of intervals equal to or higher than 0.75 hour decreased plant growth in both seasons. Thus, the use of a 23.75-hour interval in the first 15 days and a 0.25-hour interval after this period allows a decrease in energy consumption, compared to the use of a 0.25-hour interval during the whole plant cycle.